Fundamentals of cognitive science : minds, brain, magic, and evolution - Leahey, Thomas Hardy (New York, Routledge, 2023)
"Fundamentals of Cognitive Science draws on research from psychology, philosophy, artificial intelligence, linguistics, and neuroscience to provide an engaging and student-friendly introduction to this interdisciplinary field. Whilst structured around traditional cognitive psychology, the book also looks at cognitive neuroscience, and magic"--
Includes bibliographical references and index.
Keywords: Psychology; Cognition; Magic; Cognitive neuroscience